Brief antibullying intervention for adolescents in public schools - Gabriela Bottan; Simone Vizini; Pâmela Franciele Oliveira Alves; Luciano Santos Pinto Guimarães; Bianca Peixoto Nascimento; Roberta Rigatti; Elizeth Heldt (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Objectives: To assess the results of a brief antibullying intervention for adolescents in public schools. Method: This was a controlled experimental study whose subjects were 1,043 students in 5th through 9th grades from public schools in Porto Alegre/State of Rio Grande do Sul, conducted between April and November 2015. Adolescents and school teachers randomly assigned to the intervention group participated in two meetings focused on educative aspects of bullying. Outcome was assessed using the Bullying Questionnaire - victim and perpetrator version. Generalized Estimating Equations was used to evaluate the effect of the intervention. Results: Average age of subjects was 12.5 (SD=1.62) years. A total of 613 (58.7%) adolescents participated in interventions. They were compared to 430 (41.3%) participants in the control group. The study did not observe any significant difference in bullying scores after the intervention. Conclusions: This study indicates the usefulness of clarifying precisely what bullying is in schools as part of an initial approach to an educative strategy on this topic.